Galanin decreases spontaneous resting contractions and potentiates acetyl choline-induced contractions of goldfish gut. (June 2018) - Mensah, Elsie Tachie; Blanco, Ayelen Melisa; Donini, Andrew; Unniappan, Suraj
Abstract: Galanin (GAL) is a 29 amino acid peptide, first identified from the porcine intestine and widely distributed within the brain and peripheral tissues. Among GAL biological functions, its role as a potent appetite-stimulating peptide is probably the most studied. With galanin's established role in the modulation of food intake in fish, this study aims to evaluate the effects of GAL on the intestinal motility of the goldfish, Carassius auratus, using an organ bath system. Our results found that application of GAL to the organ bath causes a significant concentration-dependent decrease in the amplitude of spontaneous contractions of goldfish gut. Preincubations of intestinal strips with acetylcholine (ACh) and GAL showed that GAL increases the force of ACh-induced contractions of the goldfish gut. These results provide the first evidence for a role of GAL in gut motility in goldfish. This also suggests a crosstalk between the effects of GAL and ACh in such functions, thus pointing to a putative joint role between the two molecules. These findings offer novel information that strengthens the role of the galaninergic system in fish feeding. Highlights: GAL decreases the amplitude of spontaneous contractions of goldfish gut. Effects of GAL on gut motility are dose-dependent. GAL potentiates ACh-induced contractions of the goldfish gut.